2018
DOI: 10.1021/acs.energyfuels.7b03067
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterization of a Torrefied Wood Pellet under Steam and Nitrogen Atmospheres

Abstract: Torrefaction is a pretreatment technology for biomass to enhance its fuel quality for thermal conversion. Torrefied biomass has many advantages for handling and storage including high energy density and hydrophobicity. It also improves the grindability, which is beneficial for cofiring with pulverized coal in a power plant. This study aims to investigate the optimum operating conditions for a biomass torrefaction process using steam as a purge gas. Wood pellets were torrefied using steam heated to between 230 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The pressurized steam is, thus, likely to modify the chemical or physical structure of biomass for releasing metals as volatile compounds. Furthermore, as reported in a study on steam torrefaction at atmospheric pressure, 32 the improvement in grindability by PST was also confirmed (Figure S8). 3.1.2.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The pressurized steam is, thus, likely to modify the chemical or physical structure of biomass for releasing metals as volatile compounds. Furthermore, as reported in a study on steam torrefaction at atmospheric pressure, 32 the improvement in grindability by PST was also confirmed (Figure S8). 3.1.2.…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, the pressurized steam has a potential of effectively penetrating into biomass particles and participating in reactions occurring in torrefaction. Nevertheless, studies on torrefaction using pressurized steam have been quite limited, even including torrefaction under ambient-pressure steam or pressurized nitrogen. Those studies indicated positive effects on the fuel quality such as heating value and grindability. However, the pelletability of biomass torrefied under pressurized steam has been unknown.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 The stationary reactor is widely used for biomass torrefaction because of its simple construction and being nonpolluting to raw materials, but it causes uneven heating of torrefied materials. 19,20 Although the fluidized-bed reactor can avoid undesirable uneven heating, it may introduce problems of elutriation and segregation between biomass and inert particles, and it cannot achieve continuous processing of biomass. 21 The conveying screw, transporting or elevating granular materials, provides a possibility of achieving uniform heating and continuous production of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of operating conditions on torrefaction have been studied in many research, , but most studies were performed on laboratory-scale reactors. Thermogravimetric analysis (TGA) and gas chromatography/mass spectrometry (MS) are commonly used methods to investigate the torrefaction mechanism and its influencing factors (such as temperature, heating time, and atmosphere). , The stationary reactor is widely used for biomass torrefaction because of its simple construction and being nonpolluting to raw materials, but it causes uneven heating of torrefied materials. , Although the fluidized-bed reactor can avoid undesirable uneven heating, it may introduce problems of elutriation and segregation between biomass and inert particles, and it cannot achieve continuous processing of biomass . The conveying screw, transporting or elevating granular materials, provides a possibility of achieving uniform heating and continuous production of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen content is higher (5.1%) and the oxygen content is lower (19.2%). The energy yield is also slightly higher (69.6%) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%